WHEN TECHNOLOGY GETS IN THE WAY: INVISIBLE RISKS IN MODERN EDUCATION - Costa Júnior, João Fernando; dos Santos, Maelio Cesar Freitas; de Castro, Deyvis dos Santos Costa; Rodrigues, Sânio Pessoa; da Silva, Gleison Lima; de Sousa, Edson Canuto; Gomes, Marcelo D' Ávilla Teixeira; dos Santos, Gilvan Mendonça; Lins, Polyana Pacheco Monteiro; dos Santos, Alessandra Penha; Gonçalves, Ivone Izabel; Saldanha, Eduardo Baptista; et al. (Seven Editora, 2025)
This article addresses the invisible risks of the increasing use of technology in modern education, which, despite its evident benefits such as broadening access to knowledge and personalizing teaching, can generate negative impacts on student performance and well-being. Among the main risks discussed are distractions caused by digital devices, reduced face-to-face social interactions, and technological dependence, which compromise attention, socio-emotional development, and critical autonomy. The physical and psychological impacts of excessive screen use are also examined, such as eye strain, sleep disorders, and anxiety, which harm students' health. The article highlights the consequences for learning, such as superficial teaching and difficulty in developing critical thinking, based on studies that demonstrate inadequate pedagogical practices. To mitigate these effects, it proposes strategies for balanced and conscious use of technology, emphasizing responsible pedagogical approaches, harmonious integration with traditional methods, and school policies that guide the safe use of digital resources. The final reflection highlights the importance of balancing technology and in-person teaching, valuing human interaction and the critical thinking development of students, and points to the need for future research that delves deeper into the impacts and innovative pedagogical strategies for the effective use of technology.DOI: https://doi.org/10.56238/sevened2025.036-139